“Germany and Japan: A Legal Dialogue between Two Economies” - Kuhlmann, Axel (Zeitschrift für Japanisches Recht, 2011)
German-Japanese conference commemorating 150 years of diplomatic exchange between Japan and Germany, 20-22 October, 2011 at the Max Planck Institute for Comparative and International Private Law, Hamburg